THE ADMINISTRATION OF UNCLAIMED MONEYS IN MALAYSIA - Dewi Sulistianingsih; Mohammad Hidir Baharudin; Siti Nuruljannah Mohd Rumainor; Rahmawati Mohd Yusoff; Akmal Hidayah Halim (International Journal of Accounting, Finance and Business, 2023)
Unclaimed moneys refer to unclaimed moneys in court and moneys in companies and firms. Unclaimed moneys in Malaysia are governed by the Unclaimed Moneys Act 1965 (Act 370). The management of unclaimed moneys is wholly under the duty and responsibility of the Accountant General who is appointed by the Finance Minister as Registrar of Unclaimed Moneys. The purpose of this paper is to examine the governing law relating to the administration of the unclaimed moneys in Malaysia and the issues relating to it. The analysis is based on a qualitative and descriptive cross-sectional analysis of the governing statutes, reported cases, and data gathered from the respective administrative authorities. The research found that the unclaimed moneys for deceased in Federal Consolidated Fund is still not administered, but the moneys are not left frozen as the Minister may invest the moneys subjected to the Trustee Act 1949. However, for the unclaimed moneys in Tabung Haji, the moneys governed by Tabung Haji Act 1995 and held by the Lembaga Tabung Haji.